2001
DOI: 10.1002/kin.1048
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of a comprehensive chemical mechanism for the oxidation of methane

Abstract: A comprehensive chemical mechanism to describe the oxidation of methane has been developed, consisting of 351 irreversible reactions of 37 species. The mechanism also accounts for the oxidation kinetics of hydrogen, carbon monoxide, ethane, and ethene in flames and homogeneous ignition systems in a wide concentration range. It has been tested against a variety of experimental measurements of laminar flame velocities, laminar flame species profiles, and ignition delay times. The highest sensitivity reactions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
159
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(170 citation statements)
references
References 36 publications
6
159
0
1
Order By: Relevance
“…The ignition delay times obtained in this manner agreed with the calculated values presented in [14]. A comparison among the experimental and calculated (GRI-Mech 3.0 [17]) ignition delay times from this study and those of Petersen et al [18], Wang et al [19] and Hughes et al [20] is shown in Figure 3. The predicted values from these mechanisms agree well with the experimental values for pure methane.…”
Section: Results and Data Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…The ignition delay times obtained in this manner agreed with the calculated values presented in [14]. A comparison among the experimental and calculated (GRI-Mech 3.0 [17]) ignition delay times from this study and those of Petersen et al [18], Wang et al [19] and Hughes et al [20] is shown in Figure 3. The predicted values from these mechanisms agree well with the experimental values for pure methane.…”
Section: Results and Data Analysissupporting
confidence: 86%
“…The data fit this equation from 1007-2043 K, 0.54-48.1 MPa, and at equivalence ratios from 0.2-5.0 with a multiple coefficient of determination, r 2 , of 0.968. The Arrhenius-type expression Figure 3 Comparison among the experimental and calculated (GRIMech 3.0 [17]) ignition delay times from this study (solid lines) and those of Petersen et al [18] (dashed line), Wang et al [19] (dotted line), and Hughes et al [20] (dash/dotted line). (Equation (2)) indicates that there is a negative correlation between the ignition delay time of the methane and the pressure and the amount-of-substance fraction of oxygen.…”
Section: Results and Data Analysismentioning
confidence: 99%
“…In our case dehydrogenation stops on C 2 H 2 which is further converted to soot precursors. This is, on the other hand, the pathway typical for methane combustion model [12]. One can notice that temperature characterizing the methane pyrolysis in our models is 1,500-2,000 K whereas temperature of plasma is 4,000-5,700 K [6].…”
Section: Discussionmentioning
confidence: 54%
“…A set of 48 chemical reactions used in the model is presented in Table 1. It is based on the so called ''Leeds methane oxidation mechanism'' [11,12]. In spite the fact that we observed soot formation in the experiment, we did not include the mechanism for its formation in the table.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed homogeneous reaction scheme is based on the Leeds methane oxidation mechanism (Hughes et al, 2001), complemented and corrected by Turányi et al (2002). The mechanism has been tested against experimental data.…”
Section: Chemical Kineticsmentioning
confidence: 99%